Тривиализация песенных цитат в русском бытовом и публицистическом дискурсе - Leszczak, Oleg (Przegląd Wschodnioeuropejski, 2026)
The article is devoted to the analysis of functionally indirect quotation of song fragments in Russian domestic and publicistic discourse. Two possibilities of trivialization and adaptation of quoted statements to everyday and socially significant situations are considered – literalization of their content and referents (including formal contraction of the meaning of the phrase to a single concept), as well as functional transformation (including remetaphorization). Quoting song phrases is considered in the article against the background of the general phenomenon of creating precedent statements as autonomous linguistic analytical signs.